Sand Dune Stabilization and Management of Sandy Soils for Sustainable Biomass Production in Arid Ecosystem - Dhillon, R. S.; Jhorar, B. S.; Hooda, M. S.; Mor, R. P. (Indian Journal of Agroforestry, 2020)
The arid regions of India are characterized by hostile environment and economic conditions of the farmers in these tracts is relatively very poor due to low soil productivity. The Regional Research Station Balsamand of CCS Haryana Agricultural University, Hisar made progress in sand dune stabilization and management of these sandy soils. Notable among these include techniques of sand dune stabilization, shelterbelt plantation, season of transplanting and use of brackish water for establishment of multipurpose tree species. The survival percentage after second year was more than 85 per cent in different tree species with fourteen supplementary basin irrigation. The winter season transplantation of different tree species showed maximum survival rate. All the tree species were found superior to Prosopis cineraria, the king tree of desert, in terms of growth. The inverted pyramidal type of shelterbelt reduced the wind speed upto 36.5 per cent. The soil moisture content increased with depth in soil profile in leeward side of both shelterbelts. The tree species viz., Acacia nilotica, Dalbergia sissoo, Azadirachta indica and Prosopis cineraria could be established by using brackish water up to 200 m.e.-1 without any apparent detrimental effect on their growth.